ANALISIS TANDA DAN MAKNA POSTER FILM ‘SITI’ (2014) RUMAH PRODUKSI FOURCOLOURS FILMS - Septi Asri Finanda; M. Muhlis Lugis; Dharmawati Dewi Pamungkas (KalaTanda, 2020)
Film posters are one of the visual communication media to promote films. The film titled SITI, produced by Fourcolours Yogyakarta, is one of the Indonesian films that won an award as the winner of the best film poster at the 2015 Indonesian Film Appreciation (AFI). André Tanama. Film posters are designed to have unique, creative, and communicative values. The aim of the research is to describe the design strategy, visual elements, and the visual meaning of the SITI film poster. The research method used is a descriptive qualitative approach. The results of the research show that in designing SITI film posters, the design strategy is carried out using a communication approach and a creative approach. The visualization of the SITI film poster consists of several visual elements, a persistent female figure, and a hard worker selling jingking shellfish. Several visual objects represent scenes that occur in the film SITI. Keywords: Movie poster sign and meaning, SITI movie poster, Wood-cut Graphic.